A fungal sRNA silences a host plant transcription factor to promote arbuscular mycorrhizal symbiosis - Silvestri, Alessandro; Ledford, William Conrad; Fiorilli, Valentina; Votta, Cristina; Scerna, Alessia; Tucconi, Jacopo; Mocchetti, Antonio; Grasso, Gianluca; Balestrini, Raffaella; Jin, Hailing; Rubio‐Somoza, Ignacio; Lanfranco, Luisa (The New phytologist, 2025)
Summary Cross‐kingdom RNA interference (ckRNAi) is a mechanism of interspecies communication where small RNAs (sRNAs) are transported from one organism to another; these sRNAs silence target genes in trans by loading into host AGO proteins. In this work, we investigated the occurrence of ckRNAi in Arbuscular Mycorrhizal Symbiosis (AMS). We used an in silico prediction analysis to identify a sRNA (Rir2216) from the AM fungus Rhizophagus irregularis and its putative plant gene target, the Medicago truncatula MtWRKY69 transcription factor. Heterologous co‐expression assays in Nicotiana benthamiana, 5′ RACE reactions and AGO1‐immunoprecipitation assays from mycorrhizal roots were used to characterize the Rir2216–MtWRKY69 interaction. We further analyzed MtWRKY69 expression profile and the contribution of constitutive and conditional MtWRKY69 expression to AMS. We show that Rir2216 is loaded into an AGO1 silencing complex from the host plant M. truncatula, leading to cleavage of a host target transcript encoding for the MtWRKY69 transcription factor. MtWRKY69 is specifically downregulated in arbusculated cells in mycorrhizal roots and increased levels of MtWRKY69 expression led to a reduced AM colonization level. Our results indicate that MtWRKY69 silencing, mediated by a fungal sRNA, is relevant for AMS; we thus present the first experimental evidence of fungus to plant ckRNAi in AMS. See also the Commentary on this article by Xie & Fan, 246: 814–817.